Barriers to Early Mobility of Patients in the Intensive Care Unit of Hospitals in Kohgiluyeh and Boyer-Ahmad Province, Iran, According to the Perceptions of Physicians, Nurses, and Physiotherapists - Javad Sajadifar; Farshad Sharifi; Fatemeh Bahramnezhad (Iran University of Medical Sciences, 2023)
Background & Aims The early mobility of a patient hospitalized in the intensive care unit (ICU) is a very complicated issue and requires coordination between the departments and between all ICU staff, including physicians, nurses, and physiotherapists. Early mobilization program is safe and feasible and has positive results for the patient, medical staff, families, and health system. The present study aims to determine the barriers to early mobility of patients admitted to the ICUs of hospitals in Kohgiluyeh and Boyer-Ahmad Province, Iran. Materials & Methods This is a descriptive cross-sectional study conducted in 2020-2022. The study population consists of the ICU staff of hospitals in Kohgiluyeh and Boyer-Ahmad Province, including physicians, nurses, and physiotherapists. Sampling was done by a census method. The data were collected using a demographic form and a researcher-made questionnaire of early mobility barriers of ICU patients and analyzed in SPSS software, version 18 using descriptive and inferential statistics. Results In the present study, 174 nurses, physicians, and physiotherapists answered the questionnaire, where 57.8% were female and 59.8% were single. Among the barriers to early mobility, the patient-related barriers had the lowest mean (0.411±0.108) and cultural barriers had the highest mean (0.478±0.146). Conclusion It is necessary to investigate the barriers to early mobility of patients admitted to the ICU of study hospitals, especially the cultural barriers. In this regard, there is a need to design a clinical protocol to manage and reduce these barriers.